If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y = -4y + 24 Reorder the terms: -2y = 24 + -4y Solving -2y = 24 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. -2y + 4y = 24 + -4y + 4y Combine like terms: -2y + 4y = 2y 2y = 24 + -4y + 4y Combine like terms: -4y + 4y = 0 2y = 24 + 0 2y = 24 Divide each side by '2'. y = 12 Simplifying y = 12
| 6m^2-72+216=0 | | 2v^2-14v+12=0 | | 3x+2+6x+11+5x-1=180 | | 3y-2y(y+19)=9y-3(9-y) | | -6(4d+5)+7d=-2d | | 33y-6y=-18-36 | | -(p+17)=4p-2 | | 3x-15+2=-20 | | 10-16=12x-6x-3x-3 | | p+0.77=9.3 | | 0.3+0.6(25-c)=12 | | 5x-1=6x+11 | | 2.7h+15=0.3(10-h) | | y=4x^2-x^2 | | 200=3x+2 | | 5x-4-7x=3x+6 | | 200=3x+7 | | 9(8d*5)+13=12d-2 | | -15=-6+x | | 4r-10=2r+16 | | 5(4-2y)=8(3y-2) | | -3(6a-3)+8a=-1 | | 3.1t+7=2.6 | | 3x-6=8x-26 | | 0.8(y-5)=10 | | 5(3k-2)=4(3-5k) | | -9(2-y)-(2-y)=2 | | -x-4=3x-4 | | 6(2g-4)-(3g-7)=1 | | xy^4+x^2y=5x+3y | | 14.6=k/2.5 | | 3n+53=99 |